An Approach for Automatic Formalization of Business Rules - Kacfah Emani, C.H.; Ferreira da Silva, C.; Bruno Fiès; Zarli, A.; Ghodous, P. (Proc. of the 33rd CIB W78 Conference (International Council for Research and Innovation in Building and Construction), 2016)
This paper presentsan approachthataims to suggest toConstruction experts a formal representation of given requirements. When available as formal expressions, requirements are suitable for automatic compliance checking. The goal of conformity checking is to answer the question “which components of a building project are non-compliant to a set of construction rules?”. When we considerboth the size and the complexity of corpora of construction requirements, a computer-aided compliancechecking process would be beneficial for experts. Such checking process requires a formal representation of building projects and construction rules. Nowadays, there are various tools for the formal designing of building products obeying to the Industry Foundation Classes (IFC)standard (e.g. Revit Buildingof Autodesk, ArchiCADby Graphisoft, and ACTIVe3dby ARCHIMEN GROUP). On the other hand, to the best of our knowledge, there isn’t any tool which allows business experts to convert automatically and in a formal language, construction rules written in natural language. We propose an approach which intendsto convert automaticallynatural language requirementsinto formal expressions. This approach relies on the IfcOWL ontology and represents formalrules as SPARQL queriesusing the RAINS language asaninterimresult.RAINS is a controlled natural language(CNL), whose sentences can be transformed automatically into SPARQL queries, and as a CNL it hides the complexity of formal languages.